IN SILICO IDENTIFICATION OF EQQUS CABALLUS MIRNAS WITH THE POTENTIAL TO AFFECT HUMAN GENE EXPRESSION (Experimental biology, 2022)
miRNAs exist that are codified by non-human genomes but are still present in circulation.These miRNAs have been termed as xeno-miRNAs. XenomiRNAs in humans have been identified in various exogenous sources previously.The aim of this work is to identify xeno-miRNA from Eqqus caballus (domestic horse or in brief eca) which have analogs can bind to human genes. The MirTarget program was used to predict miRNA binding to human gene mRNAs.The homologs of eca-miRs were identified by using miRviewer online free available bioinformatic tool. It was identified 15 eca-miRNAs interacted with human mRNA genes with high complementarity, ∆G/∆Gm equal to 98-100%. The characteristics of the interaction of all known eca-miRNAs with mRNAs of human genes were identified. The total number of binding sites for 469 miRNAs are 1605, from which 907 are in CDS, 451 in 3’UTR and 247 in 5’UTR. 93 miRNAs each have one-target genes, 63 miRNAs have two target genes, 67 miRNAs have three to four target genes, and 72 miRNAs have five and more target genes. The free energy of the interaction of the considered miRNAs with the mRNAs of human genes is high and varied from -110 kj/mole to -117 kj/mole. The homology analyses revealed 140 miRNAs candidates shown to be total identical to human miRNAs sequences.
Keywords: miRNA, mRNA, milk, xeno-miRNA, eca